FAKTOR–FAKTOR YANG MEMPENGARUHI BIAYA AUDIT EKSTERNAL DENGAN RISIKO LITIGASI SEBAGAI VARIABEL INTERVENING - Arsyad Suryo Wibowo; Imam Ghozali (Diponegoro Journal of Accounting, 2017)
This study aimed to analyze the relationship between factor-factor influencing external audit fee with litigation risk as an intervening variable on manufacturing companies. Factor-factor influencing external audit fee is represented by size, complexity, and status of audit firm.. This research refers to research conducted by Nasser (2016).This study uses secondary data obtained from the financial statements of manufacturing companies listed on the Indonesian stock exchanges in 2013 - 2015. This study used as many as 64 samples with purposive sampling method. Data analysis was done by testing classical assumption, and hypothesis testing with multiple linear regression model, and path analysis. For then the result will be tested with Sobel test to know the indirect effect.The results obtained from this study are external audit costs directly influenced by company size, company complexity, firm audit size and litigation risk. litigation risk can be an intervening variable that connects size, comp, aust with audite fee.